2008
DOI: 10.1001/archpedi.162.9.828
|View full text |Cite
|
Sign up to set email alerts
|

Young Maternal Age and the Risk of Neonatal Mortality in Rural Nepal

Abstract: Objective To investigate the relationship between adolescent pregnancy and neonatal mortality in a nutritionally deprived population in rural Nepal, and to determine mechanisms through which low maternal age may impact neonatal mortality. Design Nested cohort study using data from a population-based, cluster-randomized, placebo-controlled trial of newborn skin and umbilical cord cleansing with chlorhexidine. Setting Sarlahi District of Nepal. Participants Live-born singleton infants of parity 0 or 1 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0
4

Year Published

2010
2010
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 30 publications
9
67
0
4
Order By: Relevance
“…This finding supports the results of previous studies, which have concluded that the increased risk of neonatal mortality among adolescents is largely attributable to preterm birth and the socio-economic circumstances of younger mothers. 4,16,21,27,28 Consistent with previous studies, we found a significantly lower risk of caesarean section deliveries among adolescents aged 16-19 years compared with women aged 20-24 years. 4,[29][30][31] This may be partly explained by the fact that adolescents generally have smaller babies than older women.…”
Section: Discussionsupporting
confidence: 91%
“…This finding supports the results of previous studies, which have concluded that the increased risk of neonatal mortality among adolescents is largely attributable to preterm birth and the socio-economic circumstances of younger mothers. 4,16,21,27,28 Consistent with previous studies, we found a significantly lower risk of caesarean section deliveries among adolescents aged 16-19 years compared with women aged 20-24 years. 4,[29][30][31] This may be partly explained by the fact that adolescents generally have smaller babies than older women.…”
Section: Discussionsupporting
confidence: 91%
“…The following factors, operating through these genetic and "environmental" channels, have been shown to be related to the birth weight: the sex of child -for the same gestational age boys tend to be heavier than girls (Kramer 1987); maternal ageinfants born to adolescents and women above 35 years tend to be smaller (Sharma et al 2008;Khoshwood 2005); maternal birth weight (Simon et al 2006); maternal weight (Rice and Thapar 2010;Mahanty et al 2006;Godfrey and Barker 1997;Brooks et al 1995); maternal nutrition -cumulatively, and during pregnancy (Stephenson and Symonds 2002;Prentice et al 1983); cigarette smoking (Magee, Hattis, and Kivel 2004); ethnicity (Blanc and Wardlaw 2005;Cogswell and Yip 1995); and socioeconomic conditions operating partly through some of the factors already mentioned (Cramer 1995). To elaborate on the latter effect, it has been shown in subSaharan Africa as well as other developing parts of the world, that poverty, low education, and women's lack of autonomy are related to limited or late initiation of obstetric care, irregular or incomplete immunization (e.g.…”
Section: Determinants Of Birth Weight and Estimation Strategymentioning
confidence: 99%
“…( [1][2][3][4][5][6][7][8][9][10][11][12] The adverse outcomes and complications linked to teenage pregnancy, such as the need for instrumental delivery or emergency Caesarean section, postpartum haemorrhage, prematurity, low birth weight, low Apgar score, neonatal intensive care unit (NICU) admission and perinatal mortality, (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) are significant enough to warrant further studies to delineate the cause.…”
Section: Introductionmentioning
confidence: 99%